An Isoflovonoid, Warangalone from the Stem Bark of Dadap Ayam (Erythrina variegata) - Tati Herlina; Nasrudin Nasrudin; Unang Supratman; Anas Subarnas; Supriyatna Sutardjo; Hideo Hayashi (Jurnal ILMU DASAR, 2008)
In the course of our continuing search for novel paralytic compound from Indonesian plants, the methanol extract of the stem bark of Erythrina variegata (Leguminosae) showed significant paralytic activity against the third instar larvae of silkworm (Bombyx mori). The purposes of this research were isolation and structural elucidation of paralytic compound from the stem bark of E. variegata. Using the paralytic activity following the separation, the methanol extract was separated by combination of column chromatography to yield prenylisoflavone, warangalone. The chemical structure of warangalone was identified based on spectroscopic evidence and comparison with the previous reported. The paralytic activity of warangalone showed weak activity against the third instar larvae of silkworm (B. mori).